Determinação de caminhos mínimos em aplicações de transporte público: um estudo de caso para a cidade de Porto Alegre - Bastos, Rodrigo (Universidade do Vale do Rio dos Sinos, 2013)
The increasing use of automobiles and motorcycles has caused a continuous degradation in the traffic of large cities. This scenario gets worse due to shortcomings in the current public transportation, which is entailed, in a certain way, by the lack of information provided to the user. This study shows a computing model for a public transportation user information system. Unlike other studies based on the classical Dijkstra’s algorithm, the approach makes use of the algorithm A* to solve a shortest path problem to reduce the response time so that the model can be used in an real-time web information system. The proposed model takes into account multiple criteria of decision, such as total distance traveled and number of transfers and it was evaluated with data from Porto Alegre’s public transportation. The results were compared to those ones obtained by the use of Dijkstra’s algorithm and indicate that the combination of algorithm A* with acceleration techniques allows reducing significantly the space complexity, processing time and the number of transfers.
Keywords: Sistemas de Transportes Inteligentes; Sistemas de Informação ao Usuário; Problema de caminhos mínimos; Algoritmos de busca; Intelligent Transportation Systems; User Information Systems; Shortest path problem; Search algorithms; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação